A Cultural Perspective of Conceptual Change: Re-examining the Goal of Science Education - Zhou, George (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
The goal of science education is usually meant to develop students’ basic knowledge, skills, and scientific attitudes as stated in many countries’ curriculum documents, with little consideration of what backgrounds students bring into the classroom. A cultural approach to education has challenged this universal goal of science education. This paper provides a cultural analysis of conceptual change and recommends an argument approach to teaching for conceptual advancement. It argues that the outcome of classroom discourse cannot be oriented to be a replacement of students’ intuitive conceptions with scientific notions, rather coexistence between scientific understanding and culture/experience-based views is considered to be a more reasonable and realistic goal.